ATP-induced asymmetric pre-protein folding as a driver of protein translocation through the Sec machinery - Corey, Robin A; Ahdash, Zainab; Shah, Anokhi; Pyle, Euan; Allen, William J; Fessl, Tomas; Lovett, Janet E; Politis, Argyris; Collinson, Ian (eLife, 2019)
Transport of proteins across membranes is a fundamental process, achieved in every cell by the 'Sec' translocon. In prokaryotes, SecYEG associates with the motor ATPase SecA to carry out translocation for pre-protein secretion. Previously, we proposed a Brownian ratchet model for transport, whereby the free energy of ATP-turnover favours the directional diffusion of the polypeptide (Allen et al., 2016). Here, we show that ATP enhances this process by modulating secondary structure formation within the translocating protein. A combination of molecular simulation with hydrogendeuterium-exchange mass spectrometry and electron paramagnetic resonance spectroscopy reveal an asymmetry across the membrane: ATP-induced conformational changes in the cytosolic cavity promote unfolded pre-protein structure, while the exterior cavity favours its formation. This ability to exploit structure within a pre-protein is an unexplored area of protein transport, which may apply to other protein transporters, such as those of the endoplasmic reticulum and mitochondria.
Keywords: SecA Proteins; adenosintrifosfát; SEC Translocation Channels; Protein Folding; adenosintrifosfatasy; proteiny SecA; membránové transportní proteiny; Escherichia coli; sbalování proteinů; Membrane Transport Proteins; molekulární modely; Models, Molecular; proteiny z Escherichia coli; Escherichia coli Proteins; Adenosine Triphosphatases; translokační kanály SEC; Protein Transport; Adenosine Triphosphate; Protein Precursors; proteinové prekurzory; transport proteinů